Land cover classification and change analysis in Recife-PE municipality using unsupervised classification | Classificação da cobertura do solo e análise de mudanças no município de Recife-PE usando classificação de classificação não supervisionada - Tiago Henrique de Oliveira; Josiclêda Domiciano Galvíncio; Rejane Magalhães de Mendonça Pimentel (Revista Geama, 2016)
Rapid land use changes and land cover in urban environments have large impacts on the relationship between energy and water cycles on the surface. Remote sensing techniques allow the distinction and categorization of objects in the physical and spatial point of view. The objective of this research is to quantify the land use change and land cover in the municipality of Recife-PE by unsupervised classification in multi-temporal images of the satellite Landsat 5. Was used eight images sensor Thematic Mapper (TM), Orbit and point 214/65-66 aboard the Landsat 5 satellite, obtained from National Institute for Space Research (INPE) with dates of passage on May 9, 1987, September 28, 1989, June 14, 1991, 8 September 2005, August 26, 2006, July 28, 2007, September 6, 2010 and September 25, 2011. The images were recorded, orthorectified and underwent deletion of shadow and cloud . Soon after they passed radiometric calibration and computation of reflectance. Among the main results can be cited decreased vegetation cover and consolidation of the urban area as well as the preservation of large plant fragments, like the Matas da Várzea, Curado, Barro, Jardim Uchôa e Dois Irmãos. Become important to the maintenance and preservation of the remaining vegetated areas, especially in more densely populated areas of the city of Recife.